Cleavage/polyadenylation factor IA associates with the carboxyl-terminal domain of RNA polymerase II in Saccharomyces cerevisiae. - Barillà, D; Lee, B; Proudfoot, N (2001)
The carboxyl-terminal domain (CTD) of the largest subunit of RNA polymerase II plays an important role in transcription and processing of the nascent transcript by interacting with both transcription and RNA processing factors. We show here that the cleavage/polyadenylation factor IA of Saccharomyces cerevisiae directly contacts CTD. First by affinity chromatography experiments with yeast extracts we demonstrate that the Rna15p, Rna14p, and Pcf11p subunits of this complex are associated with phosphorylated CTD. This interaction is confirmed for Rna15p by yeast two-hybrid analysis. Second, Pcf11p, but not Rna15p, is shown to directly contact phosphorylated CTD based on in vitro binding studies with recombinant proteins. These findings establish a direct interaction of cleavage/polyadenylation factor IA with the CTD. Furthermore, a quantitative analysis of transcription run-on performed on temperature-sensitive mutant strains reveals that the lack of either functional Rna14p or Pcf11p affects transcription termination more severely than the absence of a functional Rna15p. Moreover, these data reinforce the concept that CTD phosphorylation acts as a regulatory mechanism in the maturation of the primary transcript.